2011
DOI: 10.4172/2155-6121.1000106
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Term Exposure Patterns in Neonatal Intensive Care Unit Alters Immunological Outcome in Neonates

Abstract: Advances in technology have lowered the limits of viability in premature births to 24 weeks of gestation. This brought forth a new population of children, who are born 3-4 months early and spent considerable amounts of time in neonatal intensive care unit (NICU), instead of sterile environment of mother's womb. Besides, other problems associated with prematurity, these children often undergo invasive procedures resulting in mucosal inflammation and/ or injury by feeding tubes, endotracheal tubes, and prolonged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 51 publications
(58 reference statements)
0
9
0
Order By: Relevance
“…Technologies are available to challenge this paradigm in the areas of focused compound synthesis, storage and handling of compounds and information-rich assays, however, these will continue to present both excite ment and challenge for those engaged in the discovery of new drugs for some time to come. The results demonstrated that this analytical Technique are accurate, precise, specific, linear, reliable, sensitive, and fast [64].…”
Section: Resultsmentioning
confidence: 80%
“…Technologies are available to challenge this paradigm in the areas of focused compound synthesis, storage and handling of compounds and information-rich assays, however, these will continue to present both excite ment and challenge for those engaged in the discovery of new drugs for some time to come. The results demonstrated that this analytical Technique are accurate, precise, specific, linear, reliable, sensitive, and fast [64].…”
Section: Resultsmentioning
confidence: 80%
“…The relationship between blood glucose level and the levels of Na + and K + ions is complex and depends on a number of factors 1. Diabetes Mellitus causes dysnatremias2 via several mechanisms 3,4.…”
Section: Introductionmentioning
confidence: 99%
“…Some study suggests that MSC showed a fibroblast-like morphology and can be differentiated in vitro into osteogenic lineages [45]. Adult human stem cells have also been isolated or identified from human kidney, breast, pancreas, mesenchyme, liver and prostate [46].These stem cells can be used for regeneration treatment [47,48].…”
Section: Is Stem Cell Therapy the Future Of Regenerative Medicine?mentioning
confidence: 99%